Gut microbial community in Proboscis Monkeys (Narsalis larvatus): Implications for effects of geographical and social factors - Lilian Jose; Wanyi Lee; Goro Hanya; Augustine Tuuga; Benoit Goossens; Joseph Tangah; Ikki Matsuda; Vijay Subbiah Kumar (Royal Society Open Science, 2024)
Recent technological advances have enabled comprehensive analyses of the previously uncharacterized microbial community in the gastrointestinal tracts of numerous animal species; however, the gut microbiota of several species, such as the endangered proboscis monkey (Nasalis larvatus) examined in this study, remains poorly understood. Our study sought to establish the first comprehensive data on the gut microbiota of free-ranging foregut-fermenting proboscis monkeys and to determine how their microbiota are affected locally by environmental factors, i.e. geographical distance, and social factors, i.e. the number of adult females within harem groups and the number of adults and subadults within non-harem groups, in a riverine forest in Sabah, Malaysian Borneo. Using